Energy cover crops for biogas production increase soil organic carbon stocks: A modeling approach. Issue 2 (30th November 2022) - Levavasseur, Florent; Kouakou, Patrice K.; Constantin, Julie; Cresson, Romain; Ferchaud, Fabien; Girault, Romain; Jean‐Baptiste, Vincent; Lagrange, Hélène; Marsac, Sylvain; Pellerin, Sylvain; Houot, Sabine
Abstract: Energy cover crops for biogas production through anaerobic digestion (AD) are inserted between two primary crops. They replace either bare soil or nonharvested cover crops, and their management is usually intensified to produce more biomass. They allow the production of renewable energy as well as digestate, used as an organic fertilizer, without directly competing with food production. Because of the increased biomass production and export and of the return of a digested biomass to the soil, the impact of energy cover crops on soil organic carbon (SOC) is questioned. The objective of this paper was to study the difference in SOC stocks induced by the introduction of energy cover crops for AD coupled with the application of the resulting amount of digestate. We used the AD model Sys‐Metha combined with the soil C model AMG to simulate SOC stocks for 13 case studies in France, with scenarios comparing different intercrop management practices, with or without cover crops, harvested or not. Our results indicated that the higher biomass production of energy cover crops (from 6.7 to 11.1 t DM ha −1 ) in comparison with nonharvested cover crops (2 t DM ha −1 ) or bare soil led to higher humified C input (belowground input and digestate), despite the high C fraction exported in AD. This resulted in an increase in SOC stocks in comparison with nonharvested cover crops or bare soil (from 0.01 to 0.12 t C ha −1  year −1 over 30 years). The uncertainties in the model parameters did not modify these results. However, in the case of equal biomass production between energy cover crops and nonharvested cover crops, SOC stocks would be lower with energy cover crops. Abstract : The anaerobic digestion of cover crops for biogas production does not compete directly with food production and is promoted in various countries. Some questions arose regarding the effects of energy cover crops on soil organic carbon (SOC) stocks. Using a modeling approach and considering actual field practices, we showed that energy cover crops increase SOC stocks in comparison with bare soil or nonharvested cover crops due to an increase in biomass production and despite C exported for biogas production. However, nonharvested cover crops increase SOC more in the case of a similar biomass production than energy cover crops. Résumé: Les cultures intermédiaires à vocation énergétique (CIVE) pour la production de biogaz par méthanisation sont insérées entre deux cultures principales. Elles remplacent soit le sol nu, soit des cultures intermédiaires non récoltées. Leur gestion est généralement intensifiée pour produire davantage de biomasse. La méthanisation des CIVE permet la production d'énergie renouvelable ainsi que de digestat, utilisé comme engrais organique, sans entrer directement en concurrence avec la production alimentaire. En raison de l'augmentation de la production et de l'exportation de biomasse et du retour au sol d'une biomasse digérée, l'impact des CIVE sur le carbone organique du sol (SOC) est questionné. L'objectif de cet article était d'étudier la différence de stocks de carbone organique du sol induite par l'introduction de CIVE couplée à l'application de la quantité résultante de digestat. Nous avons utilisé le modèle de méthanisation Sys‐Metha combiné au modèle de carbone du sol AMG pour simuler les stocks de carbone pour 13 cas d'étude en France, avec des scénarios comparant différentes pratiques de gestion de l'interculture, avec ou sans culture intermédiaire, récoltée ou non. Nos résultats indiquent que la production plus élevée de biomasse des CIVE (de 6, 7 à 11, 1 t MS ha −1 ) par rapport aux cultures intermédiaires non récoltées (2 t MS ha −1 ) ou au sol nu conduit à un apport plus élevé de C humifié (apport souterrain et digestat), malgré la fraction élevée de C exportée dans le méthaniseur. Il en résulte une augmentation des stocks de carbone par rapport aux cultures intermédiaires non récoltées ou au sol nu (de 0, 01 à 0, 12 t C ha −1 an‐1 sur 30 ans). Les incertitudes sur les paramètres du modèle ne modifient pas ces résultats. Toutefois, dans le cas d'une production de biomasse égale entre les CIVE et les cultures intermédiaires non récoltées, les stocks de carbone seraient plus faibles avec les CIVE.